2011
DOI: 10.1007/s00113-011-2077-8
|View full text |Cite
|
Sign up to set email alerts
|

Winkelstabile, mehrdimensionale Plattenosteosynthese der Klavikulaschaftfraktur

Abstract: The treatment of comminuted shaft fractures of the clavicle by means of a multidimensional locking plate is a safe treatment option that includes early functional postoperative care with free range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They concluded that TEN is an equally effective alternate to plate fixation. Also, Dezulovic M et al 13 evaluated 35 patients treated with multidimensional, anatomical locking plate osteosynthesis for comminuted clavicle shaft fracture. They had a mean DASH score of 1.25 and a mean Constant Murley score of 98.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that TEN is an equally effective alternate to plate fixation. Also, Dezulovic M et al 13 evaluated 35 patients treated with multidimensional, anatomical locking plate osteosynthesis for comminuted clavicle shaft fracture. They had a mean DASH score of 1.25 and a mean Constant Murley score of 98.…”
Section: Discussionmentioning
confidence: 99%